A20: linking a complex regulator of ubiquitylation to immunity and human disease - Ma, Averil (2012)
A20 (also known as TNFAIP3) is a potent anti-inflammatory signalling molecule that restricts multiple intracellular signalling cascades. Recent studies in three general areas have converged to highlight the clinical and biological importance of A20. First, human genetic studies have strongly linked polymorphisms and mutations in the gene encoding A20 to inflammatory, autoimmune and malignant diseases. Second, studies in gene-targeted mice have revealed that A20 regulates multiple immune cell functions and prevents experimental diseases that closely mimic human conditions. Third, biochemical studies have unveiled complex mechanisms by which A20 regulates ubiquitin-dependent nuclear factor-κB and cell-survival signals. Taken together, these studies are revealing the importance of A20-mediated regulation of ubiquitin-dependent signalling in human disease.